Psychometric evaluation of the Chinese version of the Elderly-Constipation Impact Scale: a translation and validation study - Chen Zheng; Zhen Yang; Linghui Kong; Ziyun Gao; Tingting Lu; Huijun Zhang (BMC, 2023)
Abstract Objective The objective of this study was to translate the Elderly-Constipation Impact Scale into Chinese and to examine its reliability and validity in a population of older people suffering from chronic constipation. Methods In this study, the scale was paraphrased, back-translated, cross-culturally adapted and pre-experimented using the Brislin double translation-back-translation method to create the initial Chinese version of the Elderly-Constipation Impact Scale. A convenience sampling method was used to select 564 study participants who met the inclusion and exclusion criteria in Liaoning and Shanxi, China, to evaluate the reliability and validity of the scale. General information about the study population was using descriptive statistics; item analysis was used to screen the items of the scale. Content validity, exploratory factor analysis, and validation factor analysis were chosen to validate the scales; internal consistency, spilt-half reliability and retest reliability were used determine the reliability of the measurement scales. Results The Chinese version of the Elderly-Constipation Impact Scale contains 7 dimensions and 21 items. The Cronbach's alpha coefficient for the total scale was 0.901 and the range of Cronbach's alpha values for each dimension was 0.707 to 0.918. The split-half reliability of the scale was 0.736 and the retest reliability was 0.763. The exploratory factor analysis showed a KMO value of 0.873 and a Bartlett's spherical test X 2 value of 3499.978 (p < 0.001). A total of seven common factors were extracted, namely daily activities, treatment satisfaction, lack of control of bodily function, diet restriction, symptom intensity, anxiety and preventive actions, with a cumulative variance contribution of 77.813%. Each item had a loading value > 0.4 on its common factor. In the validation factor analysis, the model fit results were X 2 / df = 1.886, GFI = 0.910, AGFI = 0.874, PGFI = 0.654, IFI = 0.955, TLI = 0.942, CFI = 0.954, RMSEA = 0.056 and PNFI = 0.718. The model fit indicators were all within acceptable limits. Conclusion The Chinese version of the E-CIS has good reliability and validity in the chronic constipation population of elderly individuals. The results of the questionnaire can effectively and comprehensively reflect the impact of chronic constipation on the quality of life of elderly individuals. It provides a meaningful reference for identifying targets for intervention.